PENGARUH KETERAMPILAN, PENGALAMAN, DAN KEMAMPUAN SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN (Studi Kasus Pada UKM Mebel Di Dusun Nung Tenga, Desa Asemjaran, Kecamatan Banyuates, Kabupaten Sampang) - Badrus Sholeh; Budi Wahono; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study aims to determine the effect of skills, experience and ability of human resources on employee performance in furniture SMEs in Nung Tenga Hamlet, Asemjaran Village, Banyuates District, Sampang Regency. The population in this study were employees of five furniture SMEs in Nung Tenga Hamlet, Asemjaran Village, Banyuates District, Sampang District as many as 36 employees using saturated sampling techniques. Testing the hypothesis in this study using multiple linear regression analysis. The results showed that simultaneous skills, experience and ability of human resources significantly influence employee performance. Partially the skills, experience and ability of human resources have a significant positive effect on employee performance. Keywords: skills, experience, abilities and employee performance.